Cancer care in German centers of excellence during the first 2 years of the COVID-19 pandemic - Arndt, Volker; Doege, Daniela; Fröhling, Stefan; Albers, Peter; Algül, Hana; Bargou, Ralf; Bokemeyer, Carsten; Bornhäuser, Martin; Brandts, Christian H.; Brossart, Peter; Brucker, Sara Yvonne; Brümmendorf, Tim H.; et al. (Journal of cancer research and clinical oncology, 2022)
An increasing number of international studies demonstrate serious negative effects of the COVID-19 pandemic on the timely diagnosis of cancer and on cancer treatment. Our study aimed to quantitatively and qualitatively evaluate the capacities of German Comprehensive Cancer Centers (CCCs) in different areas of complex oncology care during the first 2 years of the COVID-19 pandemic.